Brand Building for Competitive Advantage in the Ghanaian Jewelry Industry - Naatu, Felicia (International Review of Management and Marketing, 2016)
Branding is a crucial component in marketing that determines the success of an organisation. However, developing a successful brand to gain competitive advantage is essentially a marketing problem in the Ghanaian jewelry industry. Globalization and competition especially from Asia and other developed parts of the world results in market share decline, firms' failure and job losses in the Ghanaian jewelry industry. The objective of this paper was to study the branding strategies of Precious Minerals Marketing Corporation (PMMC) and ERNIE'S Classic Jewelry and how that influences their competitive advantage. Primary data were obtained from management and customers of these two companies through interviews and questionnaires. Descriptive statistics were used in the analysis of the survey data. The results indicate that Research and Development, Internal Branding, Brand Positioning/promotion and Customer Orientation are the critical branding factors for competitive advantage adopted by the firms. However, Precious Minerals Marketing Company (PMMC) was found to be more competitive compared to ERNIE'S Classic Jewelry through brand building. The results have several implications and recommendations for firms' development through branding. Keywords: Branding, Competitive Advantage, Descriptive Statistics JEL Classification: M3